River Salinity and Climate Change : Evidence from Coastal Bangladesh - Dasgupta, Susmita; Kamal, Farhana Akhter; Khan, Zahirul Huque; Choudhury, Sharifuzzaman; Nishat, Ainun (World Bank, Washington, DC, 2014)
In a changing climate, saltwater intrusion is expected to worsen in low-lying coastal areas around the world. Understanding the physical and economic effects of salinity ingress, and planning adaptation, are key to the long-term development of countries for which sea level rise has been identified as a major risk from climate change. This paper presents a study conducted in Bangladesh, which quantifies the prospective relationship between climate-induced changes in sea level, temperature, rainfall, and altered riverine flows from the Himalayas, and the spread and intensity of salinization on river water in the coastal zone for 2050. The research takes into account the projected land subsidence of the Ganges Delta, as well as alternative scenarios of upstream withdrawal of freshwater. The findings indicate that climate change will cause significant changes in river salinity in the southwest coastal area of Bangladesh by 2050. These changes are likely to lead to significant shortages of drinking water in the coastal urban areas, scarcity of water for irrigation for dry-season agriculture, and significant changes in the coastal aquatic ecosystems. Changes in the availability of freshwater fish will likely affect the composition of capture fishery, although the increase in brackish water will enhance opportunities for brackish water aquaculture. Assessment of location-specific economic impacts of the changes in river salinity, identification of suitable adaptation alternatives, and costing of adaptation are high priorities for further analysis.